Embedded voices: Building a non-learning culture within a learning enrichment programme. (January 2015) - Hymer, Barry; Watkins, Chris; Dawson, Elizabeth; Buxton, Ruth
The researchers examined transcripts of comments made and dialogues engaged in by children, teachers and student teaching assistants during a 10-week enrichment programme for gifted and talented children aged 7–9 years. Attempts were made to match these utterances with the programme's aims and aspirations as expressed in a promotional document. Little evidence of match was revealed, but considerable evidence did emerge of the extent to which dominant technical-rational discourses and practices permeate even privileged and non-state-sponsored educational environments, at the expense of children's learning. Suggestions are made for foregrounding the processes of high quality pupil learning rather than the products of pupil performances in enrichment and extension programmes, and thereby for achieving greater congruence between this programme's avowed aims and practice.